Siber Güvenlikte Yapay Zekanın Rolü ve Önemi: Bir Derleme - Mıjwıl, Maad M.; Sadıkoğlu, Emre; Cengiz, Emine; Candan, Hasibe (Murat GÖK, 2022)
Yapay zeka teknolojileri, siber güvenlik de dahil olmak üzere birçok alanı kapsamaktadır. Siber güvenliğin temel amacı; bilişim sistemlerini bilgisayar korsanları tarafından gerçekleştirilebilecek yetkisiz erişim, verilerin silinmesi/değiştirilmesi gibi şantajlara karşı korumak ve siber saldırıları önlemektir. Bu çalışma da, yapay zeka teknolojilerinin temel çerçevesi ve kavramları vurgulanarak dijital ortamda siber güvenliğin sağlanması konusunda yapay zekanın rolü ve önemi anlatılmıştır. Sanal dünyada her geçen gün daha da karmaşıklaşan siber tehditler karşısında kullanıcıların mahremiyetini ve verilerini koruyabilmek için yapay zeka yöntemlerini kullanmanın gerekli olduğu sonucuna varılmıştır.

Today, artificial intelligence technologies are entering into many areas, including the area of cybersecurity, which is a branch of technology. The role of cybersecurity is to defend systems, networks and data from hacking and threats, preventing unauthorised access, tampering with, or deleting data, or blackmailing users. This article strives to determine the significance and role of artificial intelligence in achieving cybersecurity in the digital environment and seeking to preserve user data and information from the penetration and destruction of systems by highlighting the essential dimensions and concepts of artificial intelligence techniques. In this article, the authors decided to confirm the role of artificial intelligence in conducting cybersecurity for users of social networking sites. This article concluded that it is necessary to think about artificial intelligence techniques in employing them to protect the privacy and data of individuals and users across various digital platforms and in all areas.
The Role and Essence of Artificial Intelligence in Cybersecurity: A Survey
Keywords: Engineering; Mühendislik